How companies capture value from open design. (1st January 2011) - Raasch, Christina; Herstatt, Cornelius
Today, it is generally acknowledged that substantial value can be generated in online or offline developer communities external to the firm. What is less understood is how this value can be captured by commercial companies within viable business models. In this paper, we investigate business models in the field of open design, i.e., the development of tangible products according to the open source model. Our analysis rests on a pool of 30 open design projects. We find that four stylised business models can be observed in open design. They employ several value isolating mechanisms that enable profit-oriented commercial offerings in 'extremely open' settings, such as open design.